The influence of season on yield increase and lactation yield in the Ayrshire herd of Viik experimental farm - Mäkelä, Aarne (Agricultural and Food Science, 1967)
In the present paper the influence of season on the peak production, the duration of the ascending phase, the persistency of lactation, the 12 month production, and the live weight of the cows in the Ayrshire herd of the University of Helsinki experimental farm Viik are investigated. The material consists of cows calving during the period 1950—1965. During this time the indoor feeding was very intensive, satisfying all the nutritional requirements of the cows. At the same time the pastures were intensively cultivated. The size of the herd varied between 60 and 70 cows. The cows were divided into three groups: 1) spring calving cows, 2) cows calving during the pasre season, and 3) autumn calving cows. During the pasture season the peak production of cows in first lactation is c. 2 kg and of cows in later lactations c. 3.5 kg lower than during the indoor feeding period. The peak production of spring and autumn calving cows is on an average approximately the same. The duration of the ascending phase of cows calving during the pasture season is 6—10 days shorter than during the indoor feeding period. The length of the ascending phase is approximately the same for spring and autumn calving cows. The influence of season on the yield increase tangent, which is a measure of the rapidity of yield increase, is negligible. Cows calving during the pasture season and in the autumn are considerably more persistent in their lactations (P2:1-values higher) than cows freshening in the spring. The persistency values of cows calving during the pasture season and in the autumn are on an average approximately equally high. The 12 month lactation yields of autumn calving cows in the different age groups are 400—600 kg, i.e.c. 10 % higher than the corresponding values for cows freshening in spring and during the pasture season. The lactation yields of cows calving in spring and during the pasture season are on an average approximately equally high. The superiority in lactation yield of cows calving in the autumn compared to cows calving in the spring is due to the better persistency of lactation of the autumn calving cows. On the other hand the superiority in lactation yield of autumn calving cows compared to cows calving during the pasture season is due to the higher peak production of the autumn calving cows. The lactation yields of cows calving in spring or during the pasture season are approximately equally high. During the pasture season the average live weight of the cows is 20—30 kg less than during the indoor feeding period, which is due to the smaller contents of the digestive tract of the cow during the pasture season.